Genetic diversity and multiplicity of infection in Fasciola gigantica isolates of Pakistani livestock. (June 2020) - Rehman, Zia Ur; Zahid, Osama; Rashid, Imran; Ali, Qasim; Akbar, Muhammad Haroon; Oneeb, Muhammad; Shehzad, Wasim; Ashraf, Kamran; Sargison, Neil D.; Chaudhry, Umer
Abstract: Fasciola spp. are responsible for over 3 billion US dollars of production loss annually in livestock and cause widespread zoonotic disease. Nevertheless, understating of the emergence and spread of the trematode species is poor. The multiplicity of F. gigantica infection and its spread is potentially influenced by multiple factors, including the abundance of suitable intermediate hosts, climatic conditions favouring the completion of the parasite's lifecycle, and translocation of infected animals, or free-living parasite stages between regions. Here we describe the development of a 'tremabiome' metabarcoding sequencing method to explore the numbers of F. gigantica genotypes per infection and patterns of parasite spread, based on genetic characteristics of the mitochondrial NADH dehydrogenase 1 (mt-ND-1) locus. We collected F. gigantica from three abattoirs in the Punjab and Balochistan provinces of Pakistan, and our results show a high level of genetic diversity in 20 F. gigantica populations derived from small and large ruminants consigned to slaughter in both provinces. This implies that F. gigantica can reproduce in its definitive hosts through meiosis involving cross- and self-breeding, as described in the closely related species, Fasciola hepatica . The genetic diversity between the 20 populations derived from different locations also illustrates the impact of animal movements on gene flow. Our results demonstrate the predominance of single haplotypes, consistent with a single introduction of F. gigantica infection in 85% of the hosts from which the parasite populations were derived. This is consistent with clonal reproduction in the intermediate snail hosts. Grapical abstract: Unlabelled Image Highlights: To confirm the species identity of recovered Fasciola spp. To identify the presence of single or multiple genotypes per infection (multiplicity of infection) Demonstrate the spread of F. gigantica mt-ND-1 haplotypes